IMPLEMENTASI KEBIJAKAN SYARIAT ISLAM DI KABUPATEN ACEH TENGAH PROVINSI ACEH (Studi Kasus Penerapan Qanun Nomor 6 Tahun 2014 tentang Hukum Jinayat) - Hanivy Ade Clara; I Nyoman Sumaryadi; M. Irwan Tahir (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2018)
The Constitution Number 44 of 1999 concerning the Implementation of the Privileges of the Special Region of Aceh Province which defines Islamic Sharia as a demand for Islamic teachings in all aspects of life and Law Number 18 of 2001 concerning Special Autonomy in Aceh. Which is the basis for the implementation of the decisions of the Regional Government in general, in particular those that apply in Aceh are called Qanun. Qanun Number 6 of 2014 concerning Jinayat Law in its implementation is still not in accordance with the rules and has not answered the objectives of the policy. The purpose of this research is to find out and analyze the factors that influence the enforcement of Islamic law especially in the implementation of Qanun No. 6 of 2014 concerning Jinayat Law.Also to find out the strategies that can be done by the Central Aceh District Government so that the implementation of the Qanun is going well.The method used in this study is a qualitative method with a case study approach. This method is carried out through observation to obtain information about a problem,then to get an overview of an object of research. Data collection techniques in this study are observation, interviews and documentation. In this study, the authors used policy implementation theories from Van Meter and Van Horn (1975) and Bryson's strategy theory (1999).The results of the study show that the implementation of Islamic Sharia policy, especially in the application of Jinayat Law is not optimal yet.the problems faced were limited PPNS personnel to Satpol PP and WH, lack of supporting facilities and infrastructure, lack of budget allocation, lack of intense socialization to the public, and what needed to be done was to equip supporting facilities and operational activities and to disseminate them to public places, schools and so on.